A Morphometric Study of the Foramen of Diaphragma Sellae and Delineation of Its Relation to Optic Neural Pathways through Computer Aided Superimposition. (13th September 2015) - Yohannan, Doris George; Krishnapillai, Renuka; Suresh, Romi; Ramnarayan, Shobha
Abstract : The diaphragma sellae (DS) is a fold of dura that forms a partial roof over the pituitary gland. The foramen of the diaphragma sellae (FDS) is thereby a pathway for suprasellar extension of pituitary tumors. The purpose of this study was to describe the anatomical dimensions of the DS and FDS and to understand the relationship of FDS with the overlying optic chiasma. The study was conducted in 100 autopsy cases. Measurements were taken using vernier calipers. Photographs, taken before and after removal of optic pathway, were superimposed using image processing software. The results showed that the mean A-P dimension of DS was 1.17 ± 0.48 cm; the lateral dimension of DS was 1.58 ± 0.60 cm. The mean A-P dimension of FDS was 0.66 ± 0.42 cm; the lateral dimension of FDS was 0.82 cm ± 0.54 cm. The shapes of FDS were irregular (40%), transversely oval (29%), circular (13%), sagittally oval (11%), or trapezoid with posterior dimension more than the anterior one (6%) or anterior dimension more than the posterior one (1%). The margins of FDS were either well defined (31%) or ill defined (69%). The positional relation of FDS to optic chiasma was also found out.